Bibliography on Land-Locked States - Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Academic Publishers, 1986)
Keywords: Access to the sea (International law); Bibliography; Bibliography; Landlocked states; Bibliography; Marine resources conservation; Law and legislation; dept.egm; faculty_collection

Recollections of a revolution - geography as spatial science - billinge,m, gregory,d, martin,r - Martin, GJ (Journal of Geography, 1986)
tex.unique-id: ISI:A1986D537100011
Keywords: dept.egm; ⛔ No DOI found

History of geography - geographer responds - Martin, GJ (National Geographic Research, 1986)
tex.unique-id: ISI:A1986AZK9500002
Keywords: dept.egm; ⛔ No DOI found

Review: africa: partitioned africans, african regional OrganizatonsPARTITIONED AFRICANS ethnic relations across africa's international boundaries, 1884–1984 edited by AsiwajuA.I.New york: st martin's press, 1985, xii, 275pp, US29.95AFRICAN REGIONAL ORGANIZATONS edited by MazzeoDomenicoNew york: cambridge university press, 1984, x, 265pp, US42.50 - Glassner, Martin Ira (International Journal, 1986)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book review: Geopolitics of the Caribbean: Ministates in a wider world: T.D. Anderson, Praeger, New York, 1984, xiii + 175 pp., $26.95 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Book review: National interests and the military use of space: W.J. Durch (ed.), Ballinger, Cambridge, Mass, 1984, xiv + 304 pp., $28.00 - Glassner, Martin Ira (Political Geography Quarterly, 1986)
0 citations (Crossref) [2023-10-31]
Keywords: dept.egm

Management of Marine Regions - the North Pacific - Miles,e - Glassner, MI (Journal of Maritime Law and Commerce, 1986)
tex.unique-id: ISI:A1986E757600013
Keywords: dept.egm; ⛔ No DOI found

Managing the ocean - resources, research, law - richardson,jg - Glassner, MI (Marine Policy, 1986)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1986E233300007
Keywords: dept.egm

United-states arctic interests - the 1980s and 1990s - westermeyer,we, shusterich,km - Glassner, MI (Political Geography Quarterly, 1986)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1986C186100010
Keywords: dept.egm

The Emerging Marine Economy of the Pacific - Gopalakrishnan,c - Glassner, MI (Professional Geographer, 1986)
tex.unique-id: ISI:A1986A260100040
Keywords: dept.egm; ⛔ No DOI found

The new political geography of the sea - Glassner, Martin Ira (Political Geography Quarterly, 1986)
The political geography of the sea may be defined as that portion of the Law of the Sea which has a spatial or territorial component, including such matters as the territorial sea and the contiguous zone, the exclusive economic zone, international straits, the regimes of islands and archipelagos, freedom of transit for land-locked states, deep seabed mining and protection and preservation of the marine environment. It also includes larger issues not formally part of the Law of the Sea, such as the links between the Law of the Sea and Antarctica, and military uses of the sea. The new Law of the Sea (hence the new political geography of the sea) is the latest stage in a long evolution traceable to the ancient Greeks and Romans but accelerating since the 17th century. The United Nations Conference on the Law of the Sea produced in 1958 four conventions essentially codifying the existing Law of the Sea, including the new continental shelf doctrine. They were followed by the 1965 UN Convention on Transit Trade of Land-locked States. All soon proved inadequate, unacceptable or obsolescent. The Third United Nations Conference on the Law of the Sea (UNCLOS III, 1973-1982) produced a new single, comprehensive convention embodying nearly all old and new aspects of the Law of the Sea. This and related matters deserve much greater attention from political geographers than they have received thus far. © 1986.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-537-247-901-750 tex.type: [object Object]
Keywords: dept.egm

Special issue - the new political-geography of the sea - Glassner, MI (Political Geography Quarterly, 1986)
2 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1986AYH4000001
Keywords: dept.egm

Special issue - the new political-geography of the sea - panel discussion - Nanda, VP; Abrahamsson, BJ; Chiu, H; Alexander, LM; Glassner, MI; Earney, F; Engass, P; Knight, D; Jackson, R; Lynch, J; Morgan, J; Wolfe, L; et al. (Political Geography Quarterly, 1986)
tex.unique-id: ISI:A1986AYH4000007
Keywords: dept.egm; ⛔ No DOI found

Partitioned africans - ethnic-relations across africa international boundaries, 1884-1984 - asiwaju,ai - Glassner, MI (International Journal, 1986)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1986G522000011
Keywords: dept.egm